UPAYA PEMBIASAAN PUBLIC SPEAKING ANAK MELALUI PELATIHAN SENI BACA AL-QUR'AN DI MASJID AGUNG KUDUS - Ahmad Turmudzi; Primi Rohimi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
Public speaking is the skill of delivering oral messages in front of a crowd. This ability needs to be applied to children from an early age. One form of application can be through Qur'an recitation art training. By using descriptive qualitative method, this research aims to explain the practice of Al-Qur'an recitation art training held at the Great Mosque of Kudus, then analyzed the elements of public speaking contained therein. This study also aims to determine the benefits obtained by the participants, especially in familiarizing children with public speaking through Qur'an recitation training. The results showed that, 1) Qur'an recitation training at the Great Mosque of Kudus applies elements of public speaking in the learning process. It can be seen when the ustaz appoints one of the participants to recite the verses of the Qur'an with a loud voice or using a microphone in front of many people, which shows the practice of public speaking, 2) Qur'an recitation training has similarities with vocal techniques in public speaking, such as breathing techniques, articulation, and speaking speed or tempo, 3) This training also has a positive impact on children's public speaking skills, including improving vocal abilities, fostering courage and self-confidence, and developing social skills in interacting with others.